Measuring Settlement Livability in Dalam Bugis through the Lens of Clean Water and Sanitation Access - Purnama, Inda; Sugiarto, Agus; Anh, Dao Thi Ha; Jamaluddin, Jamaluddin (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2025)
This study aims to examine the spatial distribution of residential habitability levels in the Dalam Bugis Subdistrict based on the availability of drinking water and wastewater management aspects. Employing a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The data analysis involved processes of data reduction and presentation. The results indicate that the residential areas within the study region are categorized into two primary groups: habitable (lightly slum) and moderately habitable (moderate slum). The habitable residential area comprises one zone with a total area of 85.02 hectares, accounting for approximately 43% of the subdistrict’s total area, encompassing 2,416 housing units. In contrast, the moderately habitable residential areas are dispersed across four distinct zones, covering a total of 112.98 hectares or 57% of the subdistrict, comprising 1,677 housing units. These findings underscore the critical importance of enhancing access to clean water and improving wastewater management as strategic efforts to elevate residential environmental quality and support the development of adequate housing zones.